2019
DOI: 10.1088/1748-9326/ab4c61
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting assessments of ecosystem drought recovery

Abstract: The time taken for ecosystems to recover from drought (drought recovery time) is critically important for the ecosystem state. However, recent literature presents contradictory conclusions on this feature: one study concludes that drought recovery time in the tropics and high northern latitudes is shortest (<4 months) but another concludes that it is longest (>12 months) in these regions. Here we explore the reasons for these contradictory results and revisit assessments of drought recovery time. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 48 publications
3
34
0
Order By: Relevance
“…On the contrary, Yu et al () found an opposing pattern suggesting the drought recovery time is shortest in the tropics and high northern latitudes lasting for less than 4 months to recover to its pre‐drought condition. Following this controversy, a revisiting assessment on the drought recovery time was made by Liu et al () to understand the underlying reasons. Liu et al () found that the study time frame employed, methods used for drought identification, the definitions used in detecting the recovery level and consideration of non‐impactful droughts (droughts that did not show ecosystem production reduction) are main contributing factors that lead to a strong bias in understanding the drought recovery time.…”
Section: Drought Impact On Socio‐environmental Systems and Its Mitigamentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Yu et al () found an opposing pattern suggesting the drought recovery time is shortest in the tropics and high northern latitudes lasting for less than 4 months to recover to its pre‐drought condition. Following this controversy, a revisiting assessment on the drought recovery time was made by Liu et al () to understand the underlying reasons. Liu et al () found that the study time frame employed, methods used for drought identification, the definitions used in detecting the recovery level and consideration of non‐impactful droughts (droughts that did not show ecosystem production reduction) are main contributing factors that lead to a strong bias in understanding the drought recovery time.…”
Section: Drought Impact On Socio‐environmental Systems and Its Mitigamentioning
confidence: 99%
“…Following this controversy, a revisiting assessment on the drought recovery time was made by Liu et al () to understand the underlying reasons. Liu et al () found that the study time frame employed, methods used for drought identification, the definitions used in detecting the recovery level and consideration of non‐impactful droughts (droughts that did not show ecosystem production reduction) are main contributing factors that lead to a strong bias in understanding the drought recovery time. Furthermore, Liu et al () indicated that the drought recovery time is longest in some tropical regions but not in high northern latitudes.…”
Section: Drought Impact On Socio‐environmental Systems and Its Mitigamentioning
confidence: 99%
“…In general, it is still difficult to accurately estimate GPP at regional and global scales. This limitation in GPP data may cause dubious conclusions when assessing the effects of drought on GPP using a few or different GPP estimates (Liu et al, 2019). For example, Schewe et al (2019) found that current TEMs underestimate the impact of drought on GPP due to the insufficient representation of both natural processes and human management in the models.…”
mentioning
confidence: 99%
“…To identify a drought event, previous studies used the meteorological drought index (Standardized Precipitation Evapotranspiration Index, SPEI) and Drought Severity Index (DSI) (Liu et al, 2019;Schwalm et al, 2017;Yu et al, 2017). Climate data-based SPEI is easy to estimate for long-term analysis but it is not linked to plant condition (Vicente-Serrano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%